A System Dynamics Approach to Understanding the deep Magma Plumbing System Beneath Dominica (Lesser Antilles) - Solaro, Clara; Balcone-Boissard, Hélène; Morgan, Daniel Joseph; Boudon, Georges; Martel, Caroline; Ostorero, Léa (Frontiers in Earth Science, 2020)
To understand the dynamics of magmatic systems, one must first seek to characterize the time-dependent behavior of magma storage and ascent. Herein, we do this through a combination of the Crystal System Approach and careful study of Fe-Mg interdiffusion in orthopyroxene. This allows us to trace the pre-eruptive dynamics of magma plumbing systems, both in space and time. We apply this novel approach on two large silicic eruptions (about 3–5 km3 DRE/eruption) that occurred in the central part of Dominica Island (Lesser Antilles Arc): the eruptions of Layou (∼51 ka) from Morne Diablotins, and Roseau (∼33 ka) from Morne Trois Pitons-Micotrin. For the Roseau eruption, two magmatic environments (MEs) are identified on the basis of orthopyroxene composition, with a dominant reverse-zoning pattern from 50 to 54 to 54–59 mol% enstatite (En), indicating interaction with hotter magma. For the Layou eruption, three MEs are observed as represented by three populations of pyroxenes: En47-51, En51-53 and En53-58. The normal-zoning pathway from En51-53 to En47-51 is significantly registered by crystals, interpreted as convective mixing in a zoned reservoir. The reverse-zoning pathway from En47-51 to En51-53 and also En53-58 is also significantly present, supporting the mixing within the zoned reservoir but also suggesting mixing with a hotter magma, possibly stored in another part of a sub-volcanic mush. The crystal and glass compositions (melt inclusion and matrix glass) from both studied eruptions suggest heating and mixing between different magma pockets located within the mush that were the dominant process for mobilizing eruptible magma. In parallel, we constrain the associated pre-eruptive timescales by modeling the diffusive relaxation of Fe-Mg chemical gradients that originated within the zonation of the same orthopyroxene crystals. Diffusion modeling was considered along the b-axis of 66 zoned orthopyroxene crystals for these two eruptions, at a magmatic temperature of 850 ± 25°C. In light of these results, we propose that the Layou and the Roseau magma reservoirs were rejuvenated and heated by ∼25–50°C about 10 years prior to eruption by the injection of an underplating, hotter magma, creating the observed dominant reverse-zoning patterns of the erupted orthopyroxenes. We thus have evidence that silicic mush can be re-mobilized over timescales of decades prior to eruption, as previously suggested for Santorini and Taupo volcanoes.